Promocja rodziny w prawie kanonicznym. Uwagi na kanwie § 1 kan. 226 KPK - Pastwa, Andrzej (Studia Pastoralne, 2026)
Two remarks of John Paul II from his Letter to families (1994) constitute landmarks of the contemporary Magisterium de familia christiana. „The family itself – says number 19 of the document – is the great mystery of God. As the »domestic church«, it is the bride of Christ. The universal Church, and every particular Church in her, is most immediately revealed as the bride of Christ in the »domestic church« and in its experience of love: conjugal love, paternal and maternal love, fraternal love, the love of a community of persons and of generations”. This statement correlates with a part of number 17 of the said letter: „As a community of love and life, the family is a firmly grounded social reality. It is also, in a way entirely its own, a sovereign society, albeit conditioned in certain ways. This affirmation of the family’s sovereignty as an institution and the recognition of the various ways in which it is conditioned naturally leads to the subject of family rights”. As P.J. Viladrich rightly observed, a creative academic reflection on a convergence of meaning resulting from the both famous notions „domestic church” and „sovereign family” may contribute to implementation of a postulate to place family in a central position of systematics of the canon law. Christian family has an unquestionable constitutional and legal place in the Church and a society. What is at stake here is „a primary basic structure around which the people of God is build up, configured and fundamentally organised” (J. Hervada). Representatives of the so called „Spanish school” unanimously point at the canon – key to a new placement of a family in a canonical legal order. If the science of canon law still has got a task to introduce a congruent system of family law, a peculiar catalyst and a starting point of its fulfilment may be a formula of canon 226 § 1 of the Code of Canon Law which states that: „According to their own vocation, those who live in the marital state are bound by a special duty to work through marriage and the family to build up the people of God”.